Initial Assessment and Implications for Surgery: The Missed Diagnosis of Irreducible Knee Dislocation - Xu, Bin; Xu, Honggang; Tu, Jun; Guo, Ruipeng (The Journal of Knee Surgery, 2018)
Irreducible knee dislocation is a rare but devastating orthopedic emergency. Limited discussion about its characteristics has been undertaken due to its low incidence. The purpose of this study was to present a series of irreducible dislocated knees and cumulatively reviewed all existing publications in this filed. A retrospective case series study was undertaken in patients with irreducible knee dislocation. Patients' data were carefully collected and presented. Historical cases of irreducible knee dislocation in published papers were reviewed, and their diagnosis, treatment, and prognosis were summarized. Six patients with six irreducible knee dislocations were enrolled with an average age of 51.2 ± 9.7 years. Patterns of injuries were classified into KD-III M (three cases), KD-IV (two cases), and KD-V (one case). Dimple sign was presented in all cases on both physical examination and MRI. All patients received single-stage arthrotomy together with cruciate ligament reconstruction acutely. In cumulative literature review, 34 papers with 45 irreducible knee dislocations were included. KD-III M was the most familiar type of ligamentous injury (75.0%). Dimple sign was recorded in 83.7% occasions and the most frequent two trapped structures were medial retinaculum (31.8%) and MCL (43.1%). Open reduction was conducted in all cases to reduce the knee, and the prognosis of 88.0% cases was considered to be acceptable after different staged surgery. The “dimple” sign is pathognomonic but not necessary for diagnosis of irreducible knee dislocations. The general consensus for treatment is immediate neurovascular status assessment and acute open reduction.
Keywords: dimple sign; irreducible knee dislocation; Schenck classification